Influence of Alstonia Angustiloba tree water uptake on slope stability: A case study at the unsaturated slope, Pahang, Malaysia - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan; Muhammad Farhan, Zolkepli (Geological Society of Malaysia, 2023)
Although previous research has significantly enhanced our understanding of problematic and unsaturated soil behaviour and interaction with structures, there is still an urgent need to address the difficult scenarios that are met with problematic and unsaturated soils. This study examines the effects of tree water uptake at different depths and distances on the improvement of induced water uptakes caused by transpiration via mature Alstonia Angustiloba tree. This study is performed to examine the tree water uptake profile in a vegetated slope with the existence of mature Alstonia Angustiloba tree at the top and the stability of the slope during various precipitation penetration events by which the data of the tree water uptake produced within this section of the slope is recorded and implemented to evaluate the factor of safety (FOS). Slope stability analysis is further conducted to explore how plant transpiration affects slope stability. The results indicate that higher tree water uptake lead to the greatest increase of FOS of the slope up to 53% (from 2.17 to 4.57). The highest tree water uptake recorded was at the slope station with Alstonia Angustiloba tree with a depth of 0.25 m and a distance of 1.1 m from the tree. The tree water uptake utilized in this study can contribute to a carbon-free and eco-friendly approach which can be implemented globally to prevent slope failures.